Enhancing learners’ awareness of presentation literacy to stimulate interactive and creative learning in tertiary education - Baranovska-Vasiljeva, Ivona (Creativity Studies, 2024)
Learning methods play a significant role and receive more and more attention in this digital era where everyone wants something exciting, dynamic, effective, and interactive. This paper argues that one of the essential tasks of the current communication age and of a modern-day teacher is the enhancement of presentation literacy through the encouragement and development of students’ creative, communicative, and interactive skills. The article provides some of the reasons why present-day teaching should lay account on a new type learner, i.e. a net gener, and his needs as well as his expectations in the learning environment in the 21st century. The skill of effective public speaking or the practice of the commonly called presentations is brought into focus alongside. The study employed a survey on the usefulness and effectiveness of the presentation assignment which integrated TED Talks and topic-related creative activities. The research involved the students of Creative Industries study program at Vilnius Gediminas Technical University, Lithuania. As a result, a more creative and interactive learning method of delivering presentations and becoming more self-confident speakers proved to be beneficial among students. Their reflections revealed their attitude towards the effectiveness of the activity and offered insights into the learning process on how to help teachers cater to changing students’ needs. The implications of this article are relevant to all stakeholders in higher education.